Increase the level of preparedness of the special young basketball referees - Помещикова [Irina Pomeschikova] Ірина Петрівна; Пащенко [Natali Pashenco] Наталія Олександрівна; Печников [Aleksii Pechnikov] Олексій Дмитрович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> 1024x768 <![endif]–> The aim of the study was to determine the effect of training program developed in the "School for Young Arbitrators" to the level of judges specially trained in basketball. Considered indicators of the level of physical fitness, psychological state before the game, the theoretical knowledge of the rules of basketball, correct decisions in different game situations on video quality and practical judging Young Arbitrators Kharkov. In the experiment involved 11 young students suddey 1–4 courses that have been trained in the "school of young referees". Found that a specially designed program allowed young referees improve physical fitness, knowledge of the rules and their interpretations, to instill confidence in their own strength, thereby improving the quality of service games. <!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>